Resiliensi Akademik dan Keterlibatan Mahasiswa Calon Guru : Studi Transisi Pembelajaran Era Post-Pandemic - Sri Hardianti Sartika; Betanika Nila Nirbita (Universitas Pendidikan Mandalika, 2023)
The research aims to examine the effect of academic resilience on student engagement of prospective teacher students during the transition from online to offline learning. An explanatory survey with a quantitative approach was used in this research. The sample consisted of 376 students (23% male and 77% female) from prospective teacher students with the 2019-2021 entry range. The research instruments used were the Academic Resilience Scale (ARS-30) from Cassidy and the Student Engagement Scale from Gunuc and Kuzu, with some modifications. Data analysis techniques used descriptive statistical analysis and inferential statistics. The results showed that there was a significant effect of academic resilience on student engagement (p<0.05) and had an influence contribution (R2) of 57.2%. The findings of this study indicated that a high level of student involvement could optimize the learning process, and student engagement would be stronger if it were supported by high academic resilience, particularly during the transitional learning period following the pandemic.